2005
DOI: 10.1016/j.bulm.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for assessing control strategies against West Nile virus

Abstract: Since its incursion into North America in 1999, West Nile virus (WNV) has spread rapidly across the continent resulting in numerous human infections and deaths. Owing to the absence of an effective diagnostic test and therapeutic treatment against WNV, public health officials have focussed on the use of preventive measures in an attempt to halt the spread of WNV in humans. The aim of this paper is to use mathematical modelling and analysis to assess two main anti-WNV preventive strategies, namely: mosquito red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
211
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(218 citation statements)
references
References 33 publications
4
211
0
3
Order By: Relevance
“…A N U S C R I P T [4], proposed a single-season differential equation model in a mosquito-bird-human community (an isolated patch) to assess preventive strategies against WNV. Lewis et al [17] extended the models formulated in [12,13] by including impulsive events and concluded that a reduction in bird density would exacerbate the epidemic with model in [13], while it would help to maintain the epidemic on the basis of the model in [12].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 4 more Smart Citations
“…A N U S C R I P T [4], proposed a single-season differential equation model in a mosquito-bird-human community (an isolated patch) to assess preventive strategies against WNV. Lewis et al [17] extended the models formulated in [12,13] by including impulsive events and concluded that a reduction in bird density would exacerbate the epidemic with model in [13], while it would help to maintain the epidemic on the basis of the model in [12].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Lewis et al [17] extended the models formulated in [12,13] by including impulsive events and concluded that a reduction in bird density would exacerbate the epidemic with model in [13], while it would help to maintain the epidemic on the basis of the model in [12]. Blayneh et al [6] slightly modified the model in [4] to assess the impact of some anti-WNV control measures and obtained the threshold conditions for WNV outbreaks and demonstrated the existence of backward bifurcation in their model. Jiang et al [16] showed that the dynamics of the whole model in [4] were indeed determined by the four dimensional system involving only the mosquitoes and birds, and suggested that the most effective and realistic strategy to prevent the spread of WNV was to control the mosquitoes.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 3 more Smart Citations